Has Job Reservation Been Effective? Caste, Religion, and Economic Status in India* - Vani K. Borooah etal (2005)
This paper investigates the effect of job reservation on increasing the economic opportunities available to persons belonging to India's Scheduled Castes (SC) and Scheduled Tribes (ST). We estimate a multinomial logit model on employment data from the 55th NSS round to obtain the probabilities of different social groups in India being in different categories of economic status. The social groups considered are: ST (Christian); ST (non-Christian); SC; Other Backward Classes (OBC), Muslim; OBC, non-Muslim; "forward caste" Hindu (non-OBC/SC/ST Hindus); Muslims (non-OBC/SC/ST); Christian (non-OBC/SC/ST); Sikhs (non-OBC/SC/ST). The economic categories are: own account workers; regular salaried or wage workers; casual wage labourers. We use these probabilities to decompose the difference between group X and "forward caste" Hindus in the proportions of their members in regular salaried or wage employment. This decomposition allows us to attribute a proportion of this difference to "coefficient differences" between group X and "forward caste" Hindus, the remainder being due to attribute differences. We measure the effects of positive discrimination in boosting the proportions of ST/SC/OBC persons in regular salaried employment and the discriminatory bias against Muslims who do not benefit from such policies. We conclude that an alternative, and more effective, way of raising the proportion of prime-age men from the SC/ST groups in regular salaried or wage employment would be to improve their employment-related attributes.